The use of fungi in in the criminal investigation process in Iran - Samad Jamali (Forensic Science Today - Peertechz Publications, 2020)
The knowledge of forensic mycology has been formed by using the capacity of the science of fungus identification and has gradually opened its place as a tool for identifying criminals in the criminal cases of some countries. The main purpose of this study is to get acquainted with forensic mycology in the process of investigating different criminal cases and the need for the criminal system to benefit from this new method. Fungi exist in many environments, in grounds, air, air conditioners, bathrooms of houses, on wet floors, showers, dirty, and wet laundry, in dark, and humid environments as cellars, and attics and other places. Fungi can be used in criminal investigations for investigating cause of death, time of death, locating buried corpses, providing trace evidence, hallucinations, or poisonings, biological warfare and ascertaining time of deposition. In Iran, fungi have not been used in criminal investigations, although the use of fungi for these studies in the future is inevitable. During the last years many researchers have found various situations in which fungal data can provide critical evidence.